The Effects of Obesity on Drug Metabolism in Children - G. Oeser, Steffen; R.A. Rougee, Luc; C. Collier, Abby (Drug Metabolism Letters, 2015)
Obesity in children is a significant clinical concern. There are many anecdotes and case studies regarding specific reactions of obese children to medications including therapeutic failure, adverse drug reactions and/or requirements for higher weight-adjusted dosing. There isis, however, a lack of basic and clinical data dissecting the mechanisms of these effects on pharmaceutical efficacy and safety. At present it is unknown how much of the difference in drug disposition in obese children can be attributed to obesity, to maturation or to an interaction between the two. Since a major determinant of drug disposition is hepatic metabolism, here we review how obesity alters hepatic drug disposition in children. Basic as well as clinical data summarizing the current knowledge of biochemical, physiological and clinical effects of pediatric obesity on drug disposition are considered. We conclude that there is a dire need for increased research into the direct effects of obesity on absorption, distribution, metabolism and excretion, as well as changes to pharmacokinetic parameters such as bioavailability and clearance. Increased effort in this area may elucidate the effects of obesity on clinical drug disposition with sufficient detail to provide better dosing guidelines where needed for children.
Keywords: Developmental pharmacology